2011
DOI: 10.1017/s0007114511002753
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates steatosis in obese Zucker rats by decreasing fatty acid availability and reducing oxidative stress

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most common manifestations of chronic liver disease worldwide. The aim of the present study was to assess the effect of resveratrol on liver fat accumulation, as well as on the activity of those enzymes involved in lipogenesis and fatty acid oxidation in fa/fa Zucker rats. A total of thirty rats were assigned to three experimental groups and orally treated with resveratrol for 6 weeks, or without resveratrol (C: control group; RSV15 group: 15 mg/kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
100
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 49 publications
12
100
0
Order By: Relevance
“…Chang et al [26] found that BMI categories are positively correlated with an increased incidence of NAFLD, suggesting that obese patients might have an increased risk of developing NAFLD. Previous studies in rodent models have shown that resveratrol can inhibit NAFLD by decreasing body weight, as well as other obesity-related complications such as blood glucose and LDL-cholesterol [23,27]. According to the mentioned studies, anthropometric indexes have a crucial role in assessing resveratrol efficacy.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
“…Chang et al [26] found that BMI categories are positively correlated with an increased incidence of NAFLD, suggesting that obese patients might have an increased risk of developing NAFLD. Previous studies in rodent models have shown that resveratrol can inhibit NAFLD by decreasing body weight, as well as other obesity-related complications such as blood glucose and LDL-cholesterol [23,27]. According to the mentioned studies, anthropometric indexes have a crucial role in assessing resveratrol efficacy.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
“…An intraperitoneal glucose tolerance test was performed in overnight (16 h)-fasted mice. Mice were injected with a bolus of 2 g of glucose/kg body weight, and blood glucose was measured in tail vein blood at 0, 15,30,45,60,90,120, and 180 min after injection using a handheld glucose meter (Accu-Chek, Roche Applied Science). To assess whole body metabolism through indirect calorimetry, mice were individually housed in metabolic chambers (CLAMS, Columbus Instruments) for 48 h after an initial acclimatization period.…”
Section: Methodsmentioning
confidence: 99%
“…Body weight and food intake were daily recorded. The doses of polyphenols were chosen based on previous studies [39][40][41]. …”
Section: Animals Diets and Serum Biochemical Parametersmentioning
confidence: 99%